In situ testimonies: the witness of whetstones and Semai Orang Asli toponyms to the Rawa Malay slave raids - Heikkilä, Karen (ERDKUNDE, 2016)
This paper recounts toponyms and whetstones memorializing a specific episode in the history of the indigenous Semai Orang Asli of Peninsular Malaysia, namely the Prak Sangkiil or Rawa Malay slave raids. The pillage of Orang Asli settlements for the purpose of acquiring slaves remains unacknowledged in official versions of Malaysian history. Although it was the Semai ancestors who were directly victimized, the Prak Sangkiil lives on in contemporary Semai imagination as a frame of reference for current struggles. As markers of indigenous historical memory, sites, names and narratives testify to the Prak Sangkiil and other acts of violence perpetrated against the Orang Asli. The paper concludes with the idea that the validation of indigenous oral histories is necessary for the creation of more inclusive and just representations of national pasts as well as for growing understanding and reconciliation between non-indigenous and indigenous peoples.